Coordination-resolved bonding and electronic dynamics of Na atomic clusters and solid skins. Issue 44 (16th May 2015) - Bo, Maolin; Guo, Yongling; Huang, Yongli; Liu, Yonghui; Wang, Yan; Li, Can; Sun, Chang Q.
<x xml:space="preserve">Abstract</x> Atomic undercoordination shortens the interatomic bond, deepens the energy level, raises the local energy density and lowers the atomic cohesive energy of Na solid skins and clusters.